DAMPAK BROKEN HOME TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI DI RA AL MUJTAMA PAMEKASAN - Sitti Hafidatul Khofifah; Desi Ismawati (STAI Al Mujtama Pamekasan, 2026)
The family plays a crucial role in the social and emotional development of early childhood. Broken homes can potentially lead to emotional instability due to a lack of parental support and attention, which can impact a child's ability to interact socially and manage their emotions. This study employed a quantitative descriptive method with purposive sampling. Subjects included teachers and parents or guardians, with data collected using a questionnaire on children's social and emotional development. Data were analyzed descriptively based on percentages. The results indicate that children from broken homes experience difficulties interacting with peers, tend to be withdrawn, and have low self-confidence in communicating. Meanwhile, emotional development scores ranged from low to very low, indicating the absence of severe emotional disorders. These findings underscore the importance of parents and teachers in providing consistent emotional support to optimize children's social and emotional development.